Концепція перекладу Андре Лефевра та її термінологія - Кальниченко, О.А.; Зарубіна, З.В.; Kalnychenko, O.A.; Zarubina, Z.V. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2014)
У статті розглядається перекладознавча концепція бельгійського науковця Андре Лефевра, який розробив свою власну теоретичну модель дослідження художнього перекладу, розглядаючи його як одну із форм «переписування» і акцентувавши при цьому увагу не на мовних, а на культурних аспектах перекладу. У статті також йдеться про роль, яку концепція переписування відіграла у повороті перекладознавства до культури та до питань влади, та розтлумачується термінологія, яку запровадив до дослідження перекладу Андре Лефевр. В статье рассматривается переводоведческая концепция бельгийского ученого Андре Лефевра, который разработал свою собственную теоретическую модель исследования художественного перевода, рассматривая его как одну из форм «переписывания» и акцентируя при этом внимание не на языковых, а на культурных аспектах перевода. В статье также отмечается роль, которую концепция переписывания сыграла в повороте переводоведения к культуре и к вопросам власти, и объясняется терминология, которую ввел в исследования перевода Андре Лефевр. The article deals with the framework of translation of the Belgian translation scholar Andrй Lefevere who developed his own theoretical model of literary translation, regarding it as a form of “re-writing” and shifting attention from language to culture. The article also notes the role played by the concept of rewriting in the turn of Translation Studies to culture and to the issues of power and explains the terminology that was introduced in the study of translation by Andrй Lefevere.
Andrй Lefevere’s Conception of Translation and Its Terminology Explained
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; перекладознавство; Лефевр Андре; поворот до культури; заломлення; переписування; покровительство; текстові та концептуальні ґратки; культурний капітал; Translation Studies; Lefevere А.; cultural turn; refraction; rewriting; patronage; textual and conceptual grids; cultural capital